Temuan Manik-Manik Bekal Kubur Di Situs Pangkungparuk, Kecamatan Seririt, Kabupaten Buleleng - Dwi Andriyani, Ni Made; Agung Bawono, Rochtri; Sapta Jaya, Ida Bagus (Humanis, 2016)
North Bali is an area in the northern part of the island of Bali that posses many archaeological remains associated with the burial site. On of them is a diverse variety of goods burial treasures such as beads contained in Pangkungparuk, Seririt buleleng. These archaeological remains are evidence of a civilization that has taken place in this region. The purpose of this study is to determine the typology and technique of manufacture and raw materials used in the manufacture of beads contained in Pangkungparuk village, district Seririt Buleleng regency.  The theories used in this research are the theory of typology and structural functional theory. The method used in this study is as follows, the data collection phase is done by observation, interview and literature study, then the second phase is data processing by analyzing data used analytical techniques articatural, contectual analysis, qualitative analysis and comparative analysis. From the analysis it can be concluded that the beads contained in the Site Pangkungparuk have various shapes of beads like round, oblate, double cone which cut the top, double cone concave, elliptical, ovate, flat, and disc cylinder. Technique used in making beads contained on the site pangkungparuk are shaping  techniques for spherical beads and printing techniques for double cone beads, while the raw material for making beads vary from natural raw material such as of shells, rocks and pearls as well as raw material made of glass and bronze metal.